(untitled) (CIPEEX, 2025)
The transition between adolescence and young adulthood is a potentially conflicting phase full of questions, discoveries and challenges, a dynamic that in its development can result in maturity and resilience, or even, as very commonly observed due to numerous risk factors, is capable of triggering mental disorders such as anxiety and depression. The aim of this study was to analyze the prevalence of symptoms of anxiety and depression in young university students. This is a literature review based on bibliographic material obtained from indexed databases such as SciELO, LILACS, The Library of UNICAMP, BVS, and MEDLINE. Data collection involved a thorough analysis of the selected literature in order to obtain a complete understanding of the topic. The results obtained through this research highlight that this study scenario reveals a worrying reality that affects the mental health and well-being of young university students. It is concluded from the analysis of the articles that, unfortunately, anxiety and depression are common mental health problems among university students and have increasingly affected these graduates.